Identification of Ghost Moving Detections in Automotive Scenarios with Deep Learning - Martinez Garcia, Javier; Prophet, Robert; Fuentes, Michel Juan Carlos; Ebelt, Randolf; Vossiek, Martin; Weber, Ingo (IEEE MTT-S International Conference on Microwaves for Intelligent Mobility (ICMIM 2019), 2019)
We introduce a method to classify ghost moving detections in automotive radar sensors for advanced driver assistance systems. A fully connected network is used to distinguish between real and false moving detections in the occupancy gridmaps. By using this architecture, we combine the local Doppler information, along with the spatial context of the surrounding scenario to classify the moving detections. A proof of concept experiment shows promising results with data from a test drive in an urban scenari